PROSPECTS FOR USING THE RESULTS OF GENETIC TESTING IN INSURANCE - Suvorova , Ekaterina; Nikiforov , Vladimir; Sergeevich , Sergey; Zaikin , Sergey; Bartsits , Henri (Revista Inclusiones, 2020)
The prospects of using the results of genetic testing in the assessment of insurance risk when concluding an insurance contract are very relevant. When determining whether it is appropriate for insurers to use genetic information in assessing insurance risk in personal insurance, two main problems arise – the scientific reliability of genetic information and its actuarial significance. The purpose of the study is to determine the prospects for using the results of the genetic study to assess insurance risk in the field of personal insurance. The methodological basis of the research was made up of dialectical, teleological, axiological, logical, formal-legal and comparative-legal methods. The article gives the authors’ definition of genetic information as the information related to various genetically determined states, which is obtained by the direct study of DNA. The study presents the conclusion that the most informative results to assess insurance risk in personal insurance are those of targeted sequencing to assess the relevance and demand of information resulting from the genetic study. For personal insurance, it is necessary to take into account several factors. Some of these factors are related to the characteristics of the insurance itself (a type of insurance, sales channels), while others concern the characteristics of the corresponding population, and still, others relate to the methods of genetic research used.